Public Funding of Political Parties - Christian Schultz; Ignacio Ortuno-OrtÍn (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper concerns public funding of parties. Parteis receive public funds depending on their vote share. Funds finance electoral campaigns. Two cases are investigated. In the first, some voters are policy motivated and some are ?impressionable? ? their vote depends directly on campaign expenditures. In the second, campaigning is informative and all voters are policy motivated. Public funds increase policy convergence in both cases. The effect is larger, the more funding depends on vote shares. When campaigns are informative, there may be multiple euqilibria. Intuitively, a large party can stay large since it receives large funds.
Keywords: 330